BAYRAK KUSHCUOGLU: Great Poet of the Ahl-e Haqq - Hunkari Sufi Order Belief (Journal of Alevism-Bektashism Studies, 2021)
After Sultan Ishak (Shk), the founder of the Ahl-e Haqq- Hunkari Sufi order belief, Shah Ibrahim took the leadership of the Order. Bayrak Kushcuoglu is the poet and most famous bard of the Shah Ibrahim period. Referring to Zencan- Sultaniye, the capital of the Iranian Ilhanli state, in his poems and belonging to the Shah Ibrahim era are strong evidences that Bayrak Kushcuoglu lived in the first half of the 14th century. The 24 Great Poets, named “in Turkish as söyleyici, in Persian as guyende, in Arabic as kelâmgu”, expressed the belief with Turkish poems from the start. The Great Poets are: 1- Bayrak Kuşçuoğlu (Bayrak Kushcuoglu), 2-Kul Veli, 3-Kuloğlu (Kuloglu), 4-Kalender, 5-Hasan, 6-Şahsuvaroğlu (Shahsuvaroglu), 7-Nemmame, 8-Ali, 9-Yunus, 10-Ağaoğlu (Agaoglu), 11-Şeyhi Can (Sheyhi Can), 12-Yadigar, 13-Kamber, 14-Budak, 15-Ulu Baba, 16-Amir (Emir), 17-Kulu (Kuli), 18-Kul Kasım, 19-Mezidoğlu (Mezidoglu), 20-Gündüz, 21-Fethi, 22-Turabi, 23-Mahmud (Mahmudoglu), and 24-Ahmed. (Undoubtedly, there are poets who appeal to other ethnic groups in the following periods.) The circles related to the Ahl-e Haqq think that Kul Veli and Kuloglu are related to Haci Bektash Veli, and Yunus is related to Yunus Emre. Among the followers of the belief, especially Turkish-Atesh Beyli community is the biggest community whose average ratio is in between 30-40 % according to the various estimates. While the reformist works compatible with Shia belief of Nimatullah Jayhunabadi (1871-1920) and his son Nurali Elâhi (Nur Ali Shah, 1895-74), popular writers of the Ahl-e Haqq belief, became widespread in Iran, Ahl-e Haqq intellectuals from Tabriz had to explain the truths of the belief (Orthodox/ mainstream). Although Sarânjâm information is still alive in the oral memory of the Ahl-e Haqq community, there were no other Sarânjâm except one dated 1843, which Minorsky obtained among the personal sources of Ahl-e Haqq intellectuals from Tabriz, or any other Sarânjâm book of equivalent value. If there were, Baba Tahir-i Üryan and Sail, the poet of the long poem that explained the belief of the Ahl-e Haqq of Sarânjâm book, would have been known.